STRATEGI PEMANFAATAN ELEARNING DAN TELEEDUKASI UNTUKPEMERATAAN PENDIDIKANKESEHATAN DI INDONESIA (TinjauanLiteratur dan Rekomendasi Kebijakan) - Muhammad Riza; Made Hery Santosa (LPPM STIKES Mataram, 2025)
Introduction: Equitable and high-quality health education serves as a crucial foundation for ensuring fair healthcare services in Indonesia. Faced with geographic challenges and significant disparities in educational infrastructure, the utilization of technologies such as e-learning and tele-education emerges as a strategic alternative to expand access to health education, particularly in 3T regions (frontier, outermost, and underdeveloped areas). This article analyzes the benefits, challenges, and implementation strategies of these two approaches in the context of higher health education in Indonesia. E-learning offers flexibility in time and space, cost efficiency, and access to global learning resources. Meanwhile, tele-education facilitates continuous training and real-time cross-regional collaboration. However, barriers such as limited digital infrastructure, low technological literacy, and underdeveloped regulations remain significant challenges. This article proposes several strategic recommendations, including infrastructure enhancement, human resource training, regulatory strengthening, and the development of a national tele-education platform. Through a holistic and collaborative approach, e-learning and tele-education can serve as key catalysts in realizing inclusive, equitable, and sustainable health education in Indonesia.